THE USE OF NONVERBAL IMMEDIACY BEHAVIORS IN THE FIRST-YEAR ENGLISH CLASSROOMS AT FELTE, ULIS, VNU AND ITS INFLUENCE = ỨNG DỤNG CỬ CHỈ THÂN THIỆN CỦA GIÁO VIÊN VỚI SINH VIÊN NĂM NHẤT Ở FELTE, ULIS, VNU VÀ TÁC ĐỘNG CỦA NÓ - Bùi, Lệ Hương (2020)
Teacher nonverbal immediacy is a valuable pedagogical instrument which helps building a positive teacher-student relationship. However, while the topic has long been thoroughly studied in the West, it has not received adequate attention to in Asian contexts, particularly in EFL classes in Vietnam. For this reason, the research was carried out with the hope to fill the gap. The main objectives of the study are to figure out the frequently used nonverbal immediacy behaviors of teachers at first-year classrooms, as well as teachers’ and first-year students’ perceptions of its influences. A multiple-case study was utilized with the participation of two first-year English teachers and their students to investigate the problem. The data was collected through the three sources: questionnaires, interviews, and observations. Descriptive and content methods were used to analyze the data collected. Comparisons between the two cases were also made. The research discovered the nonverbal immediacy behaviors which were often used by the teachers belong to kinesics, paralanguage, and proxemics types. In terms of the tool’s impact, both teachers and students believed that nonverbal immediacy helps create a pleasant learning environment and increase students’ affection towards their teachers. As a result, students become more interested in the subject and willingly participate in in-class activities and comply with their teachers’ demand. Moreover, immediate teachers are also evaluated highly by their students.